The Effect of Phytoremediation Using Duckweed (Lemna minor) on Ammonia Levels in Catfish Farming Wastewater in Boyolali - Prayogi, Eko; Indrawan, Muhammad; Hawali Abdul Matin, Hashfi (Waste Technology, 2024)
Farming activities, especially catfish Farming, as carried out by the community in Kampung Lele, Boyolali, Indonesia cannot be separated from producing waste. Water pollution caused by catfish farming waste can be identified through increased ammonia levels. This research aims to determine whether the density of duckweed (Lemna minor) can influence changes in ammonia levels in liquid waste from catfish Farming and to determine the ammonia levels in liquid waste from catfish Farming after treatment with duckweed. The research is phytoremediation research using duckweed. The research used a completely randomized design in data collection carried out with 6 variations (0 plants, 150 plants, 300 plants, 450 plants, 600 plants, 750 plants) for 15 days starting from the first day and continuing every 2 days. The repetition carried out in the research was 4 repetitions which were based on the Federer formula. The data obtained were analyzed using two way ANOVA analysis and further tested with Duncan's post hoc test using the SPSS application. The results obtained in the form of ammonia levels after treatment decreased, namely 0.6 ppm on A150, 0.5 ppm on A300, 0.5 ppm on A450, 0.45 ppm on A600, and 0.4 ppm on A750. The density of duckweed can influence changes in ammonia levels in liquid waste from catfish Farming, through two way ANOVA analysis which obtained a sig value. equal to 0.00 or < 0.05, then there is a difference in the average ammonia based on density and time, so that in Duncan's post hoc follow-up test we found variations in A750 on the 11th day with 0.475 ppm ammonia and A600 on the 15th day with ammonia 0.45 ppm meets quality standards.